The seasonal cycle of lower-tropospheric gravity wave activity at Davis, Antarctica (69°S, 78°E) - Simon Alexander; Damian Murphy (2015)
A VHF wind-profiling radar located at Davis in coastal East Antarctica (69°S, 78°E) collected data from September 2009 to August 2011 in the lower troposphere. Gravity wave activity is quantified using the radar’s wind velocity variances. ERA-Interim and Antarctic Mesoscale Prediction System (AMPS) forecast output are used to understand the gravity wave activity in the context of the synoptic-scale meteorology and to identify the likely source of the observed gravity waves. The seasonal cycle of lower-tropospheric gravity wave activity (2.0–3.2-km altitude) obtained from the radar data for waves with ground-based periods of 16 min–12.8 h reveals a maximum in winter and a minimum in summer. The largest gravity wave activity corresponds in time to the presence of a surface depression centered north of Davis that directs strong northeasterly winds along the Antarctic coastline. Case studies indicate that these winds interact with an ice ridgeline located around 60 km northeast and upwind of Davis. This interaction between synoptic northeasterly winds and the ridgeline results in the formation of orographic gravity waves, which are observed in the Davis radar data as large wind velocity perturbations.